EXPLORING THE INFLUENCE OF WORK-TO-VENTURE ROLE CONFLICT ON HYBRID ENTREPRENEURS' TRANSITION INTO ENTREPRENEURSHIP IN INDONESIA - Matriadi , Faisal; Ruchiyat, Endang; Budi Raharja , Arif (KRIEZ ACADEMY : Journal of development and community service, 2024)
Abstract This research aims to examine the influence of role conflict between main job and side business on the transition of hybrid entrepreneurs to full-time entrepreneurship in Indonesia. Hybrid entrepreneurs are individuals who run a side business while still maintaining their main job as their main source of income. Role conflict may arise due to the dual demands of both roles, which may affect the hybrid entrepreneur's motivation, commitment, and ability to transition to full-time entrepreneurship. This research uses a combined approach between literature study analysis and online surveys. First, a detailed search was conducted in academic databases to identify current and relevant information on role conflict and the transition to entrepreneurship. Literature study analysis is used to build a strong conceptual framework. Next, an online survey was distributed to hybrid entrepreneurs in Indonesia to collect primary data on experiences, perceptions and challenges faced in the transition to full-time entrepreneurship. The research results show that role conflict between main job and side business influences the motivation and commitment of hybrid entrepreneurs in deciding to switch to full-time entrepreneurship. Hybrid entrepreneurs tend to experience pressure and stress because they have to divide their attention and time between their main job and side businesses. Value conflicts between professional obligations and entrepreneurial ambitions may also interfere with hybrid entrepreneurs' commitment to their side businesses. Strategies used by hybrid entrepreneurs to overcome role conflict include effective time management, use of productivity tools, psychological strategies such as meditation or relaxation, task delegation, and role integration between main job and side hustle. Hybrid entrepreneurs are also strongly influenced by the external environment, including regulatory factors and infrastructure support. Business-friendly regulations and good infrastructure support facilitate the transition of hybrid entrepreneurs to full-time entrepreneurship by reducing the administrative and operational burdens faced.